2021
DOI: 10.1200/jop.20.00002
|View full text |Cite
|
Sign up to set email alerts
|

Breaking News of Cancer Diagnosis: A Qualitative Study on the Experiences and Emotional Needs of Patients With Cancer in a Multiethnic Asian Setting

Abstract: PURPOSE: The breaking of news of a cancer diagnosis is an important milestone in a patient’s cancer journey. We explored the emotional experiences of patients with cancer during the breaking of news of a cancer diagnosis and the arising needs in a multiethnic Asian setting with limited supportive cancer care services. METHODS: Twenty focus group discussions were conducted with 102 Asian patients with cancer from diverse sociodemographic backgrounds. Thematic analysis was performed. RESULTS: While most particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…The findings on the relationship between awareness of diagnosis and prognosis and distress have implications for provider-patient communication. Communication about the diagnosis between practitioners and patients and their families has been explored in another Asian setting [20] . Wong et al found that sensitive and empathetic patient–physician communication during the “breaking news” of a cancer diagnosis may mitigate a patient's emotional distress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings on the relationship between awareness of diagnosis and prognosis and distress have implications for provider-patient communication. Communication about the diagnosis between practitioners and patients and their families has been explored in another Asian setting [20] . Wong et al found that sensitive and empathetic patient–physician communication during the “breaking news” of a cancer diagnosis may mitigate a patient's emotional distress.…”
Section: Discussionmentioning
confidence: 99%
“…Communication about the diagnosis between practitioners and patients and their families has been explored in another Asian setting. [20] Wong et al found that sensitive and empathetic patient-physician communication during the "breaking news" of a cancer diagnosis may mitigate a patient's emotional distress. Future research could focus on how communication about the diagnosis between practitioners and patients and their families in India may affect a patient's distress with the ultimate aim to develop communication approaches to reduce the emotional distress.…”
Section: Implications For Psycho-oncology Practice and Researchmentioning
confidence: 99%
“…Communicating about concerns and decision making is important during all phases of treatment and supportive care for cancer 22,23 . A patient-centered communication approach needs to be developed to reduce the emotional distress to patients and their families following a cancer diagnosis 24 .The results were also supported by the ndings in Belgium and Italy where patients also provided good understanding of the disease condition they were going through 10 .…”
Section: Discussionmentioning
confidence: 80%
“…Denial, anger, sadness and depression are common reactions to cancer diagnosis 6, 25 . Receipt of a cancer diagnosis is often deemed as bad news because it is widely regarded as synonymous to a death sentence 24 . This is particularly so because cancer is a life threating illness often associated with a lot of physical disability such as loss of body functions, change in physical appearance, disruption of family and personal life plans, recurrence or progression of the disease and high symptom burden 6,10,11,26 .…”
Section: Discussionmentioning
confidence: 99%
“…Evidence revealed that persons with a family history of cancer were also relatively less shocked by the news of a cancer diagnosis. 2,3 Psychosocial Support from Healthcare Workers Patients and caregivers could benefit from support from having a good working relationship with the healthcare workers. In particular, it seems that the presence of this therapeutic relationship made the staff more approachable to patients and carers, promoting interaction and information-seeking.…”
Section: Emotional Distress During the Breaking Of Bad Newsmentioning
confidence: 99%